The Sleuth’s Migrations in Recent British and American series (2000-2014) - Dominique SIPIÈRE (E-REA)
This article examines the migrations and stability of the ever-present figure of the Sleuth in recent TV series, specifically from the year 2000. After suggesting a few tools that could be used to classify narratives in a corpus of 20 series, it finds clear differences between British and American stories (authors, titles, real life material, status of the character). It finally focuses on the remarkable stability of the sleuth’s social background and gender and of his status as a Public Servant.